The power and democracy research project, University of Iceland: Project management details - Gunnar Helgi Kristinsson; Sjöfn Vilhelmsdóttir (University of Iceland, 2018)
From the article: The Power and Democracy Research Project was a five-year (2014-2018) research project at the School of Social Sciences, University of Iceland. It was established through a decision of the university council and funded by the University of Iceland Centennial Fund. It is a study of power and democratic governance in Iceland focusing on the legislature, executive and judicial powers, public policy and administration, as well as on the actors and participants in the system, such as political parties, interest groups, the media and the public.